The whole fatigue crack propagation life prediction of Ni-based single crystal super-alloy specimen with single hole based on EIFS and 'Fish-eye' theory. (September 2021) - Xue, Xiangzhen; Li, Wenxian; Jia, Jipeng; Liu, Jian; Di, Linjie
Highlights: A prediction model which can predict the whole fatigue crack propagation life of the structure under multi-axial stress fatigue was proposed in this work. The fatigue crack propagation life of Ni-based single crystal super-alloy specimens with a single hole was predicted, and it was verified by finite element simulation. The effects of load and initial crack length on the fatigue life of single-hole nickel-based single crystal super-alloys were discussed through finite element simulation. Under the same loading stress condition, the higher the proportion of the long crack stage in the crack propagation, the faster the fracture speed of the sample. Abstract: In this work, based on the 'Fish-eye' theory and EIFS method, a prediction model of the whole fatigue crack propagation life of the predictable structure under multi-axial stress fatigue is proposed. Then, the fatigue crack propagation life of single-hole nickel-based single crystal superalloy samples under nine working conditions was predicted and verified by finite element simulation. Finally, the effects of three loads and three initial crack lengths on the fatigue crack propagation life of single-hole nickel-based single crystal superalloy were discussed by finite element simulation. The results show that the analysis results of the theoretical model and the finite element model proposed in this work are basically consistent under certain conditions. It is found that the fatigue crack propagation life of the initial crack stage, short crack stage and long crack stage accounts for 2%, 6%–10% and 90% of the whole crack propagation fatigue crack propagation life, respectively. Under the same loading stress condition, the higher the proportion of short crack stage in crack propagation is, the faster the fracture speed of the sample is. At the same time, the progressive crack propagation process of single hole specimen under fatigue load can be seen through the calculation results of finite element model. The above conclusions provide a good theoretical reference for the design and fatigue crack propagation life prediction of nickel-based single crystal superalloy turbine blades with cooling film holes.